A survey of intrusion detection techniques - Chandran, Sharanya; Senthil Kumar, K (International Journal of Engineering and Technology, 2018)
In todayâ€™s world, the number of companies is increasing day by day that help end users to express opinion i.e. social media management, to watch news, payment applications, retail, ecommerce etc. There are large amount of forms, which take personal informationâ€™s like username, password, social security number, credit card, debit card and account information. Thus the applications are vulnerable to security issues like phishing attacks, denial of service attacks, cross-site scripting attack and many more. This paper provides literature review of work done in these areas and their respective mitigations.Â